Smart Sustainable City: Concept, Aspects and Indices - afshar hatami; farzaneh sasanpour; alberto ziparo; mohammad soleymani (تحقیقات کاربردی علوم جغرافیایی)
Increased urbanization, population growth and socio-economic and environmental problems besides growth and development of ICT at the global level are the sign of the 21st century. The contradiction between economic growth and environmental protection, encountering ultra-modern citizens with industrial cities and lack of responsibility to current citizens has led to a smart sustainable city that thanks to ICT such as IoT following to solve mentioned problems. This paper beside introducing smart sustainable approach as a counterpoint to Neoliberal approach, assessing emergence, evolution, aspects, indices, and differences between similar approaches like smart city. This research from the view of aim is basic research and from the view of nature and research method is descriptive analytic one. The results of the research indicate that also there is no universal definition of smart sustainable city, but there is an agreement on the final goal to obtain sustainable development. The reason for this necessity is the third wave of sustainability and crisis of social, economic and environmental challenges in the context of the cities. Also, primary focus of these definitions is equity and social inclusiveness, quality of life, efficiency, flexible infrastructure, ICT and environment protection. Furthermore, there was such a futuristic gap in the definition of smart sustainable city that a new definition presented based on future study approach. In contrast to similar approaches, the core of the smart sustainable city is ICT and environment protection. Also, results shows that for implementation of this aprroah inaddtion to use theory of change, future study and systems theory, should consider the slogan of “think globaly and act localy” and localization of smart sustainable approach based on social, economic, political and futuristic condition of Iranian metropolises.